Identification of Factors Causing Acute Respiratory Infection (ARI) of Under-Fives in Community Health Center Work Area in North Jayapura Sub-District - Reychell Mirino; Dary Dary; Rifatolistia Rifatolistia (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2022)
Background: Acute Respiratory Infection (ARI) is an acute infection of the upper and lower respiratory tract of organs. This infection is caused by the virus, fungi, and bacteria that begin with fever and one or more symptoms such as throat pain, difficulty swallowing, flu, and wet or dry cough. Riskesdas (Basic Health Research) categorizes Papua province in five highest areas with the infectious disease of air such as ARI and Pneumonia. Based on the annual data of Jayapura Public Health office of disease prevention and control sector reported that ARI was included in ten highest types of infectious diseases in Jayapura city suffered by under-fives. Objective: This research aimed to identify the factors caused by the IRA in the Community Health Center work area in North Jayapura Sub-district, Jayapura City, Papua Province. Methodology: A descriptive quantitative method with cross-sectional research design was used in this study. Sample of 100 under-fives in the Community Health Center of North Jayapura Sub-district were selected for this study. The technique was purposive sampling and the data collections were questionnaires and observation (done in the respondent’s houses). This research was done in Juni to August 2019. Results & Discussion: The results were presented through the table form and showed that the causes of ARI were from the under-fives, family, and environment. The conclusion of this research: smoking behavior of family is the biggest causative factor of ARI.